Bioekologi Potensi Pemanfaatan Cendawan Beauveria bassiana di Lahan Pertanaman Kacang Panjang dan Bawang Merah dalam Mengendalikan Hama Terinventarisasi - Dimas Ganda Permana Putra; Zenita Afifah Fitriyani; Mega Darmi Novita; Sri Purwanti (Jurnal Pertanian Terpadu, 2026)
Entomopathogenic fungi Beauveria bassiana hold significant potential as an environmentally friendly biopesticide while simultaneously enhancing the vegetative growth of horticultural crops. This study aimed to evaluate the effect of B. bassiana application on the growth of yardlong bean (Vigna unguiculata sesquipedalis) and shallot (Allium ascalonicum), as well as to identify infected insect pests under field conditions. The experiment was conducted in Mojokerto Regency from June to September 2025 using a randomized block design (RBD) with a single factor, consisting of four levels of B. bassiana concentration (A0 = control, A1 = 10⁶ spores L⁻¹, A2 = 10⁷ spores L⁻¹, A3 = 10⁸ spores L⁻¹) and five replications. Observed parameters included plant height and leaf number at 14, 21, 35, and 42 days after planting (DAP). Analysis of variance revealed significant treatment effects on vegetative growth. In yardlong bean, treatments A2 and A3 produced the highest average plant heights, 340.05 cm and 344.39 cm at 42 DAP, while A2 yielded the highest number of leaves (21.06 leaves). In shallot, treatment A3 produced the tallest plants (43.04 cm) with leaf number comparable to the control, indicating the biostimulant role of B. bassiana in enhancing plant vigor. Field observations identified insect pests infected by B. bassiana from the orders Coleoptera, Lepidoptera, and Hemiptera, characterized by white mycelial growth. These findings confirm that B. bassiana is not only effective as a biological control agent against diverse insect orders but also functions as a biostimulant that promotes vegetative growth of horticultural crops. Its application provides an integrative strategy for integrated pest management (IPM) and supports sustainable agriculture in the upstream area of Kromong II watershed.